STRESS AND COPING AMONG PUBLIC PROSECUTORS - Valickas, Gintautas; Vanagaitė, Kristina (Teisė, 2015)
The article analyses Lithuanian prosecutors’ (n = 349) work-related stress, its main sources and coping strategies, as well as the relations of stress, coping strategies and prosecutors’ socio-demographic characteristics. The participants completed the “Prosecutors’ experienced stress” questionnaire developed by us and the “Coping with stress” questionnaire developed by G. Valickas etc (2006, 2010). The obtained results have shown that different work-related situations caused moderate stress experienced by prosecutors. The prosecutors’ experience of stress is related with the size of city or town where they were working, division of the service (regional, district and Prosecutor General’s Office), as well as the dependence to different district services. After encountering with stress prosecutors are most likely to apply the problem solving coping strategy and least likely – emotional discharge coping strategy. The coping strategies are related with the sex, family status, size of city or town where they were working and the dependence to different district services. Furthermore, the more stress prosecutors have to deal with, the more likely they apply the various coping strategies (in that case in all work-related situations they are most likely to apply the emotional discharge and avoidance coping strategy). The gathered data suggests that stress is a sufficiently relevant (in separate work-related situations more than third part of prosecutors experience strong stress) and universal (not related with sex, age and previous work experience) topic for Lithuanian prosecutors, so prosecution service leaders should give more attention for it.